»Ko bi bil pri Trojici, tudi ti ne bi bil socialist …« - Toš, Marjan (Časopis za zgodovino in narodopisje, 2024)
In the decade before the First World War, municipal committees in rural areas in Slovene Styria – except in the Maribor area – were mostly in Slovene hands. The Germans and the Germanizers, however, had a firm grip on most of the towns (Maribor, Celje, Ptuj, Slovenska Bistrica, Ormož) and the squares of the time, including Sv. Lenart in Slovenske gorice. The Germans had two other “fighting organisations” as a firm basis for their activities, the Schulverein and the Sudmark. Although they differed slightly in outlook, the first, the Schulverein, being German liberal and the second anti-Semitic, the two complemented each other in their work of extermination. In Sv. Lenart, the Schulverein was extremely offensive, since the Germans in the market had political and economic power in their hands. There was no Schulverein in Sv. Trojica, but the economically most powerful people of the market were also Germans. After the turn of the 19th and 20th centuries, in the decade before the First World War, the physician and writer Dr. Alojz Kraigher lived in Sv. Trojica in the Slovenske gorice region. In 1914 he published Kontrolor Škrobar (Controller Škrobar). This interesting, literary picture of the ethnic situation in the Slovenian Goriška countryside, even after 110 years, carries a vibrant message about the “national misery” in these places and calls for a new Škrobar.
Keywords: Cankar; Germans; Kraigher; Lenart; Nemci; Slovenci; Slovenes; Sv. Trojica.; Škrobar; Weixl